APPLICATION OF ANALYTICAL HIERARCHY PROCESS METHOD IN BEAUTY STORE PURCHASE DECISION SUPPORT SYSTEM - Desy Natalia; Maria Alicia; Abdus Sihab Patoni (Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
This study the study aims to contribute to the broader field of consumer behavior and offer strategic insights for businesses operating in Indonesia's dynamic beauty industry. This study focuses on identifying the priority criteria influencing consumer purchasing decisions in beauty shops, utilizing the Analytical Hierarchy Process (AHP) method as a decision support system. The quantitative research was conducted using primary data collected through interviews. The findings of the study reveal that price, promotions/discounts, product completeness, and service quality are the most significant factors driving consumer purchasing decisions. This study contributes to the field by demonstrating the application of AHP in optimizing retail strategies, thereby offering valuable insights for businesses aiming to enhance customer satisfaction and competitive advantage.